2015
DOI: 10.1007/s40820-015-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Template-Free One-Pot Synthesis of Mn3O4 Nanostructures as Electrochemical Supercapacitors

Abstract: In this paper, we report an effective, simple, and cost-effective strategy of electrochemical deposition to prepare hausmannite Mn3O4 thin films for the applications of supercapacitors. Various precursor concentrations and deposition durations were manipulated to tailor the surface morphologies of Mn3O4 nanostructures and to optimize their electrochemical performances. The Mn3O4 samples prepared at 0.05 M Mn(NO3)2 solution for 30 min delivered a large gravimetric specific capacitance of 210 F g−1 at a current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…High performance energy-storage devices, as an important part in the applications of renewable energy, have attracted more and more attentions from scientific communities [1][2][3]. Electrochemical supercapacitor has long been considered as an attractive energy-storage device because of its advantages such as high power density, fast charging/discharging rate, long cycle life and high reliability [4].…”
Section: Introductionmentioning
confidence: 99%
“…High performance energy-storage devices, as an important part in the applications of renewable energy, have attracted more and more attentions from scientific communities [1][2][3]. Electrochemical supercapacitor has long been considered as an attractive energy-storage device because of its advantages such as high power density, fast charging/discharging rate, long cycle life and high reliability [4].…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] For example, Mondal et al [15] have reported the synthesis of Mn 3 O 4 nanoparticles anchored to multiwall carbon nanotubes (MWCNT) composites with high specific capacitance of 441 F g À1 at 2 mV s À1 scan rate and excellent cycling stability of 98 % after 1000 cycles. [18,19] On the other hand, Polypyrrole (PPy) has drawn significant interest in supercapacitor application due to its excellent properties such as highly conductive ( % 100-10,000 S m À1 ), high doping/dedoping rate during charge/discharge process, flexible, low cost and highly scalable. Zhang et al [17] have reported the synthesis of graphene/Mn 3 O 4 nanocomposites with a promising specific capacitance of 326.9 F g À1 and an outstanding cycling stability of 94.6 % for 1000 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to achieve superior performance, it is essential to design the electrode materials with novel structure that possess a high surface area. [18,19] On the other hand, Polypyrrole (PPy) has drawn significant interest in supercapacitor application due to its excellent properties such as highly conductive ( % 100-10,000 S m À1 ), high doping/dedoping rate during charge/discharge process, flexible, low cost and highly scalable. [20][21][22] In our present study, we have employed the electrodeposition method to deposit PPy films on carbon fiber due to its several advantages among other methods such as scalability, ease of fabrication, high adhesive nature of the substrate, controllable morphology and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…37 It is both low cost and environmentally friendly. 38 It does not have a high conductivity with literature putting it between 10 -7 -10 -8 S cm -1 . 38 This phase of manganese oxide is a highly stable form relative to the other manganese oxides.…”
Section: Infiltration Of Lsm/ysz Cathode Using Manganese Oxidementioning
confidence: 95%
“…38 It does not have a high conductivity with literature putting it between 10 -7 -10 -8 S cm -1 . 38 This phase of manganese oxide is a highly stable form relative to the other manganese oxides. 37 It is commonly used in supercapacitor studies due to its high theoretical specific capacitance of around 1400 Fg - 1 38 as well as used as a catalyst for oxidation of methane and CO. 37 It is possible that this oxide could decrease the polarization resistance by aiding in the oxygen ion diffusion and oxygen reduction.…”
Section: Infiltration Of Lsm/ysz Cathode Using Manganese Oxidementioning
confidence: 95%